Analytical Methods for the Assessment of Maillard Reactions in Foods - Singla, Rajeev K. (Chemistry of Foods,, 2018)
This Brief provides an overview of different analytical methods and techniques for the qualitative and quantitative evaluation of Maillard Reactions and their reaction products in foods during processing and storage. Reliable methodology for the investigation of Maillard Reactions and their products are of utmost importance in food analysis: since Maillard Reactions can on the one hand be desirable and advantageous, influencing the colors, flavors and odors of food products, they can on the other hand also produce detrimental compounds afflicting the consumers' health (e.g. furfurals, furosine, or acrylamide). This Brief introduces different analytical methods, which can be used to investigate and characterize Maillard Reactions and their products in foods, including for example capillary electrophoresis, high performance liquid chromatography, gas chromatography with mass spectrometric detection, UV-VIS spectrophotometry, fluorescence, electronic nose, gravimetric systems, and many more. The chapters exemplify how the analytical techniques can be applied for assessing and evaluating different Maillard Reaction products in foods. Readers will find basic information, as well as practical hints and guidelines for application in their own laboratory.